THE NECESSARY OF LABOR FORCE IN THE TWO CONVENTIONAL AND ECOLOGICAL AGRICULTURAL SYSTEMS - Alexandra-Marina BRĂTULESCU (MANOLACHE); Ionuț-Laurențiu PETRE; Liviu MĂRCUȚĂ; Alina Gabriela MĂRCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this paper, it is desired to establish the differences regarding the agricultural labor force needs for two different systems, namely the conventional and the ecological system. In the first part of the paper, in quantitative and qualitative terms, we will analyze data on labor force evolution in Romanian agriculture, using the data provided by the National Institute of Statistics. This first analysis supports the determination of the existing labor force in agriculture in order to determine whether this can be sufficient for both conventional and organic farming systems. In the second part of the paper, the specific labor force needs will be determined for some cereal crops analyzed in parallel in both conventional and ecological systems. With the help of the indicators in the technological sheets, it will be possible to achieve an average of labor force between crops in order to determine the specific differences between the labor needs between the two agricultural systems.